Stability and Change as Simultaneous Experiences in Organizational Life - Leana, Carrie R.; Barry, Bruce (Academy of Management Review, 2000)
Organizations and individual employees increasingly are pursuing change in how work is organized, how it is managed, and in who is carrying it out. At the same time, there are numerous individual, organizational, and societal forces promoting stability in work and employment relations. Here we discuss change and stability and the forces pushing individuals and organizations to pursue both. We argue that some level of tension between stability and change is an inevitable part of organizational life and that this tension must characterize research on work and organizations.